2008
DOI: 10.1093/treephys/28.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Acer saccharum canopy trees and saplings to P, K and lime additions under high N deposition

Abstract: Heavy atmospheric nitrogen (N) deposition has been associated with altered nutrient cycling, and even N saturation, in forest ecosystems previously thought to be N-limited. This observation has prompted application to such forests of non-N mineral nutrients as a mitigation measure. We examined leaf gas-exchange, leaf chemistry and leaf and shoot morphological responses of Acer saccharum Marsh. saplings and mature trees to experimental additions of non-nitrogenous mineral nutrients (dolomitic lime, phosphorus +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 102 publications
1
47
0
Order By: Relevance
“…Inorganic, extractable organic and microbial pools of N and P were determined using chloroform-fumigation and potassium persulfate oxidation (Basiliko et al 2009 (Table 1A). This is generally consistent with prior soil measurements and high N deposition in the Haliburton Highlands region (Gradowski and Thomas 2008). Relative to other forests with coarse-textured soils elsewhere in Ontario and Canada, soils in our study had slightly higher mean rates of in situ N 2 O emissions (Basiliko et al 2009, Peichl et al 2009).…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…Inorganic, extractable organic and microbial pools of N and P were determined using chloroform-fumigation and potassium persulfate oxidation (Basiliko et al 2009 (Table 1A). This is generally consistent with prior soil measurements and high N deposition in the Haliburton Highlands region (Gradowski and Thomas 2008). Relative to other forests with coarse-textured soils elsewhere in Ontario and Canada, soils in our study had slightly higher mean rates of in situ N 2 O emissions (Basiliko et al 2009, Peichl et al 2009).…”
Section: Introductionsupporting
confidence: 92%
“…Anthropogenic N deposition is an important disturbance affecting many forest regions including in eastern North America, potentially saturating tree nutrient requirements (Gradowski and Thomas 2008), and/or soil processes (Watmough 2010). Nitrogen deposition can increase foliar and litter N concentrations, N mineralization, nitrification, and denitrification rates; ultimately leading to NO 3 -leaching and downstream eutrophication, and enhanced soil losses of N 2 O (Watmough 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional N from atmospheric deposition, in combination with increased global atmospheric CO 2 concentrations and temperatures, is projected to enhance ANPP (Mohan et al, 2007). Nitrogen deposition may alter nutrient regimes in many ecosystems by alleviating N limitation (Gradowski and Thomas, 2008); however, N deposition could also promote leaching of calcium (Ca) and other base cations (Izuta et al, 2004;Perakis et al, 2006), and paradoxically of N itself (Brookshire et al, 2007). Since N limitation in temperate forests is broadly assumed (Finzi and Canham, 2000), tests of resource limitation often include only correlations of production to N, even when other resource measures (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Our transplant assays of T. landbeckii between sites showed that when plants from different source populations were grown under similar conditions of nutrient availability, the plants adjusted their elemental stoichiometry to the new environmental conditions by increasing nutrient uptake. These results suggest that T. landbeckii respond to their local environment in a similar way as phytoplankton and other terrestrial plants across environmental gradients (see Güsewell 2004;Hall et al 2005;James and Richards 2006;Bott et al 2008;Gradowski and Thomas 2008). Phenotypic plasticity may optimize plant functioning in a given environment by influencing the plant's ability to acquire new resources and grow successfully under various nutrient regimes (Sardans et al 2006;Nicotra et al 2007).…”
Section: Discussionmentioning
confidence: 87%